Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1074/jbc.m205812200
|View full text |Cite
|
Sign up to set email alerts
|

Cystamine Inhibits Caspase Activity

Abstract: Huntington's disease (HD) is an autosomal dominant neurodegenerative disorder caused by an abnormally expended polyglutamine domain. There is no effective treatment for HD; however, inhibition of caspase activity or prevention of mitochondria dysfunction delays disease progression in HD mouse models. Similarly administration of cystamine, which can inhibit transglutaminase, prolonged survival of HD mice, suggesting that inhibition of transglutaminase might provide a new treatment strategy. However, it has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(24 citation statements)
references
References 40 publications
1
21
0
2
Order By: Relevance
“…In our cellular model, the formation of ␣-synuclein aggregates was significantly reduced by CTM. Interestingly, in addition to its role as a tTGase inhibitor, CTM blocks caspase 3 activity and increases cellular glutathionine levels, suggesting that it may prolong neuronal survival (62). Based on these observations, CTM or a related compound with a similar mechanism of action would be a promising pharmacological tool to be tested in PD models.…”
Section: Discussionmentioning
confidence: 99%
“…In our cellular model, the formation of ␣-synuclein aggregates was significantly reduced by CTM. Interestingly, in addition to its role as a tTGase inhibitor, CTM blocks caspase 3 activity and increases cellular glutathionine levels, suggesting that it may prolong neuronal survival (62). Based on these observations, CTM or a related compound with a similar mechanism of action would be a promising pharmacological tool to be tested in PD models.…”
Section: Discussionmentioning
confidence: 99%
“…In animal models, cystamine has a neuroprotective effect [41], and β-mercaptoethanolamine is a registered drug used in the treatment of cystinosis and currently in trial for treatment of Huntington chorea [42]. Other actions of cystamine have also been reported, including interaction with matrix metalloproteinases, which are known to inhibit tTG activity [43], as well as inhibition of caspase 3 and antioxidant activity [44]. Cystamine has thus, in addition to its ability to inhibit tTG, multiple other actions in vivo, and cautious interpretation of the present results is needed.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of the present study was to test whether infusion of the tTG inhibitor cystamine is able to prevent inward remodelling in vivo. Cystamine is a substrate of transglutaminases that instead of enhancing the formation of cross-links binds covalently to the active site to act as a competitive inhibitor of tTG [22], although it also has other actions [23, 24]. Furthermore, we investigated whether cystamine would be able to inhibit outward remodelling, where the experiments with tTG knockout mice had indicated that this would not be inhibited [15].…”
Section: Introductionmentioning
confidence: 99%
“…TG is a therapeutic target for several neurodegenerative disorders. Cystamine, which inactivates TG, inhibits other thiol-dependent enzymes such as caspases (43) and thus plays an important role in AGE-mediated IL-8 release and cell death, which means that it might be an important therapeutic molecule in neuroprotection. Secretion of several proteolytic enzymes might also trigger AGE-mediated inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%